Early detection of colorectal cancer using symptoms and the ColonFlag: case-control and cohort studies - Holt, TA; Virdee, PS; Bankhead, C; Patnick, J; Nicholson, BD; Fuller, A; Birks, J (F1000Research, 2023)
Background Early detection of colorectal cancer confers substantial prognostic benefit. Most symptoms are non-specific and easily missed. The ColonFlag algorithm identifies risk of undiagnosed colorectal cancer using age, sex and changes in full blood count (FBC) indices. The aim of this study was to investigate whether the ColonFlag detects undiagnosed colorectal cancer prior to the recording of symptoms in general practice.